What is a good job? : a new measure of labor-market success - Jencks, Christopher [Verfasser]; Perman, Lauri [Verfasser]; Rainwater, Lee [Verfasser] (My University, 1988)
"No currently available index allows investigators to estimate the overall desirability of specific jobs. With data collected in the 1980 Survey of Job Characteristics, an index of job desirability (IJD) can be constructed to fill this gap. The IJD incorporates 13 nonmonetary job characteristics along with measures of earnings and weigths all job characteristics according to their effects on workers' judgements about how "good" their current jobs are compared with an average job. While earnings are the most important single determinant of a job's desirability, the 13 nonmonetary job characteristics together are twice as important as earnings. Unlike occupational status and earnings, the proposed index explains almost the entire effect of race, sex, educational attainment, and experience on job ratings. It also explains almost all the variation in job ratings provided by workers in different occupations. Furthermore, taking account of nonmonetary job characteristics more than doubles the estimated level of labor-market inequality. White skin, male gender, favorable social origins, high educational attainment, and extensive labor-market experience are also worth two to five times more when one considers both monetary and nonmonetary payoffs than when one considers money alone." (author's abtract) ((en)) Ziel der Untersuchung war es, die Attraktivität von Berufen insgesamt zu messen. Die Befragten sollten schätzen, wie "gut" die von ihnen ausgeübte Tätigkeit und eine Reihe weiterer Berufe zu bewerten ist. Die wichtigste Einzeldeterminante ist demnach das Einkommen, während nichtmonetäre Arbeitsplatzmerkmale zusammen doppelt so bedeutend sind. (IAB)
Was ist ein guter Arbeitsplatz?
Keywords: G 2.3 Wandel von Arbeit & Wirtschaft; G 2.4.1 Bildungs- und Berufswege; G 2.4.4 Biografiegestaltung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; Berufsprestige; Einflussfaktor; Beruflicher Status; Messung; Einkommen; Tätigkeitsmerkmal; Quantitative Angaben